No difference in gluteus medius activation in women with mild patellofemoral pain - O'Sullivan, Keiran; Herbert, E.; Sainsbury, David; McCreesh, K.; Clifford, A. (Human Kinetics Publishers INC, 2012)
CONTEXT: The gluteus medius (Gmed) is proposed to consist of 3 functional subdivisions (anterior, middle, and posterior). Gmed weakness and dysfunction have been implicated in numerous lower extremity disorders, including patellofemoral pain syndrome (PFPS). PFPS is a knee condition that frequently occurs in females and is associated with activities such as squatting and stair climbing. There is a lack of evidence for the role of the subdivisions of the Gmed in females with and without PFPS. OBJECTIVE: To compare muscle activation in the 3 Gmed subdivisions during 4 weight-bearing exercises in women with and without PFPS. DESIGN: Single-session, repeated-measures observational study. SETTING: University research laboratory. PARTICIPANTS: Convenience sample of 12 women with PFPS and 12 age- and gender-matched asymptomatic controls. INTERVENTION: Participants performed 4 weight-bearing exercises (wall press, pelvic drop, step-up-and-over, and unilateral squat) 3 times while surface electromyography (sEMG) activity of the Gmed segments was recorded.MAIN OUTCOME MEASURES: sEMG muscle activity for each functional subdivision of the Gmed during each weight-bearing exercise was analyzed using a mixed between-within-subjects ANOVA (post hoc Bonferroni). RESULTS: No statistically significant differences in muscle activation were found between the PFPS and healthy participants (P = .97). Furthermore, there were no statistically significant differences between the exercises (P = .19) or muscle fibers (P = .36) independent of group analyzed. However, the activation of the subdivisions varied according to the exercise performed (P = .003). CONCLUSIONS: Similar levels of muscle activation were recorded in the Gmed subdivisions of the PFPS and healthy participants during the different exercises. This is the first study to examine all 3 Gmed subdivisions in PFPS. Future studies using larger sample sizes should also investigate onset and duration of muscle activation in all Gmed subdivisions in both healthy individuals and those with PFPS.